Cardiometabolic risk factors in MASLD patients with HCC: the other side of the coin - Meroni, Marica; Longo, Miriam; Dongiovanni, Paola (Frontiers in Endocrinology, 2024)
Metabolic Dysfunction-Associated Steatotic Liver Disease (MASLD) constitutes the commonest cause of chronic liver disorder worldwide, whereby affecting around one third of the global population. This clinical condition may evolve into Metabolic Dysfunction-Associated Steatohepatitis (MASH), fibrosis, cirrhosis and hepatocellular carcinoma (HCC), in a predisposed subgroup of patients. The complex pathogenesis of MASLD is severely entangled with obesity, dyslipidemia and type 2 diabetes (T2D), so far so nutritional and lifestyle recommendations may be crucial in influencing the risk of HCC and modifying its prognosis. However, the causative association between HCC onset and the presence of metabolic comorbidities is not completely clarified. Therefore, the present review aimed to summarize the main literature findings that correlate the presence of inherited or acquired hyperlipidemia and metabolic risk factors with the increased predisposition towards liver cancer in MASLD patients. Here, we gathered the evidence underlining the relationship between circulating/hepatic lipids, cardiovascular events, metabolic comorbidities and hepatocarcinogenesis. In addition, we reported previous studies supporting the impact of triglyceride and/or cholesterol accumulation in generating aberrancies in the intracellular membranes of organelles, oxidative stress, ATP depletion and hepatocyte degeneration, influencing the risk of HCC and its response to therapeutic approaches. Finally, our pursuit was to emphasize the link between HCC and the presence of cardiometabolic abnormalities in our large cohort of histologically-characterized patients affected by MASLD (n=1538), of whom 86 had MASLD-HCC by including unpublished data.